2012
DOI: 10.1016/j.jbiomech.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing whole-body kinematics to minimize valgus knee loading during sidestepping: Implications for ACL injury risk

Abstract: The kinematic mechanisms associated with elevated externally applied valgus knee moments during non-contact sidestepping and subsequent anterior cruciate ligament (ACL) injury risk are not well understood. To address this issue, the residual reduction algorithm (RRA) in OpenSim was used to create nine subject-specific, full-body (37 degrees of freedom) torque-driven simulations of athletic males performing unplanned sidestep (UnSS) sport tasks. The RRA was used again to produce an optimized kinematic solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 39 publications
(63 reference statements)
1
97
0
3
Order By: Relevance
“…Torso lateral flexion and rotation produce similar effects on the moment arm of the knee abduction moment. A simulation study of sidestep cutting has demonstrated how the knee abduction moment is sensitive to the centre of mass position,23 and this may explain the effect of the torso kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Torso lateral flexion and rotation produce similar effects on the moment arm of the knee abduction moment. A simulation study of sidestep cutting has demonstrated how the knee abduction moment is sensitive to the centre of mass position,23 and this may explain the effect of the torso kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal control training was analysed because recent evidence shows a link between proximal segments and ACL injury14 15 and knee loading 19 27. When the exercise descriptions were not clear, the primary author (DS) and second author (GDM) had discussions until a classification agreement was reached.…”
Section: Methodsmentioning
confidence: 99%
“…68 12 15 16 A computer monitor displayed a 30 cm arrow to direct participants to perform the straight-run or change of direction running tasks. During unplanned running tasks, the direction arrows were triggered by the athlete running through timing gates situated along the approach pathway.…”
Section: Methodsmentioning
confidence: 99%
“…First, reduce the size of the loads applied to the knee by changing an individual's posture or technique during sidestepping 12 1416. Second, increase the strength and/or activation of the muscles crossing the knee capable of protecting it when loads are elevated 14 17…”
Section: Introductionmentioning
confidence: 99%